Applications of Micro/Nanotechnology in Ultrasound-based Drug Delivery and Therapy for Tumor - Sun, Suhui; Wang, Ping; Sun, Sujuan; Liang, Xiaolong (Current medicinal chemistry, 2021)
Ultrasound has been broadly used in biomedicine for both tumor diagnosis as well as therapy. The applications of recent developments in micro/nanotechnology promote the development of ultrasound-based biomedicine, especially in the field of ultrasound-based drug delivery and tumor therapy. Ultrasound can activate nano-sized drug delivery systems by different mechanisms for ultrasound- triggered on-demand drug release targeted only at the tumor sites. Ultrasound Targeted Microbubble Destruction (UTMD) technology can not only increase the permeability of vasculature and cell membrane via sonoporation effect but also achieve in situ conversion of microbubbles into nanoparticles to promote cellular uptake and therapeutic efficacy. Furthermore, High Intensity Focused Ultrasound (HIFU), or Sonodynamic Therapy (SDT), is considered to be one of the most promising and representative non-invasive treatment for cancer. However, their application in the treatment process is still limited due to their critical treatment efficiency issues. Fortunately, recently developed micro/nanotechnology offer an opportunity to solve these problems, thus improving the therapeutic effect of cancer. This review summarizes and discusses the recent developments in the design of micro- and nano- materials for ultrasound-based biomedicine applications.